Analysis Of Price Fluctuation Of Curly Red Chili (Capsicum annum L.) In Kendari City - Sudirman, Muhammad Yunus Hidayat; Bafadal, Azhar; Zani, Munirwan (International Journal of Technology and Education Research, 2023)
The purpose of this study is to know in general the description of curly red chili price fluctuations in Kendari city and to find out the development of curly red chili prices in Kendari city in 2022. This research uses a descriptive analysis technique that is used to determine production developments, as well as review the price of red chili curls in the city of Kendari. The research uses price data sources at the consumer level in 2022 from markets in the city of Kendari which are obtained through official government websites, including the BPS (central statistical agency) Kendari city. The results of this study show the large fluctuations in the price of curly red chilies in the city of Kendari in 2022 with the tendency for the highest curly red chili prices to be in July of 59,441 compared to November of 34,598. The factors that influence price fluctuations of curly red chilies are the weather which causes curly red chilies to only be planted for one season, rainy weather also hampers the distribution of curly red chilies resulting in an increase in the price of curly red chilies and that makes the price of curly red chilies in one region to another not the same. In addition, the process of planting curly red chilies is less than optimal, causing decreased productivity